The Influence of Return on Asset, Firm Size, and Earnings Per Share on Underpricing With Debt to Equity Ratio as a Moderating Variable in Companies That Conduct an IPO on the Indonesian Stock Exchange - Mandayani, Marsela Siti; Yulianti, Eka (SEAN Institute, 2024)
The purpose of this research is to determine the effect of financial information on underpricing in companies conducting Initial Public Offerings. The variables used in this research include Return on Assets (ROA), Firm Size (FS), Earning Per Share (EPS), and Debt to Equity Ratio (DER). The population studied involved companies that conducted an IPO and were listed on the Indonesian Stock Exchange in 2018-2022. Sampling was carried out using a purposive sampling method, with a total of 195 companies as samples. Data analysis was carried out through the MRA test using Eviews 10 software. The research results showed that Return On Assets and Firm Size had a negative effect on Underpricing. Meanwhile, Earning Per Share has no effect on Underpricing. Apart from that, the Debt To Equity Ratio can moderate the influence of Return On Assets and Earning Per Share on Underpricing, but cannot moderate the influence of Firm Size on Underpricing. Simultaneous test results show that the variables Return On Assets, Firm Size, and Earning Per Share simultaneously influence Underpricing.